2012
DOI: 10.1038/nrc3263
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer factors in hormone-dependent cancers

Abstract: Pioneer factors are a special class of transcription factor that can associate with compacted chromatin to facilitate the binding of additional transcription factors. The function of pioneer factors was originally described during development; more recently, they have been implicated in hormone-dependent cancers, such as oestrogen receptor-positive breast cancer and androgen receptor-positive prostate cancer. We discuss the importance of pioneer factors in these specific cancers, the discovery of new putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
203
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 45 publications
6
203
0
Order By: Relevance
“…6d). FOXA1, a central transcription factor of prostate cancer biology, coordinates AR binding and promotes tumour progression 31,32 . We observed a significant overlap of the 5-hmC regions with FOXA1-binding regions and K4me1-modified regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6d). FOXA1, a central transcription factor of prostate cancer biology, coordinates AR binding and promotes tumour progression 31,32 . We observed a significant overlap of the 5-hmC regions with FOXA1-binding regions and K4me1-modified regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ectopic Sox2 expression or a higher level of its expression could activate previously silent programs to establish competence for tumorigenesis, perhaps analogous to cell reprogramming. Furthermore, FoxA and GATA factors are involved in a variety of hormone-dependent cancers, such as estrogen receptor-positive breast cancer and androgen receptor-positive prostate cancer (Zaret and Carroll 2011;Jozwik and Carroll 2012). In breast cancer, FoxA1 expression is a significant predictor of cancer-specific survival in patients (Badve et al 2007).…”
Section: Pioneer Factors In Disease Progressionmentioning
confidence: 99%
“…Chromatin decompaction Fakhouri et al 2010 Mitotic bookmarking (human) Binding to mitotic chromatin Caravaca et al 2013 Hormone-dependent cancer progression (human) Recruitment of hormone receptor Zaret and Carroll 2011;Jozwik and Carroll 2012 In vitro reconstituted nucleosome or nucleosome array…”
Section: Updike and Mango 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, the nature and prevalence of FOXA1 mutations in prostate cancer has not been comprehensively studied. The present analyses have revealed that FOXA1 mutation occurs at a rate of 3%-4% among primary prostate cancer and CRPC cases.…”
mentioning
confidence: 99%